Aerobic bacteria in oral cavity of Lancehead snakes (Bothrops atrox) with stomatitis - Pereira, Heloisa Castro (2017)
Stomatitis is a common disease found on snake farms, and Gram-negative bacilli are the main etiological agents that play an important role as secondary sources of viral or parasitic infections. The purpose of this work was to identify the aerobic bacteria in the oral cavity of Bothrops atrox with stomatitis. Samples for microbiological examination were collected from 12 snakes bred on a commercial snake farm for venom extraction. Samples of the secretion in the oral cavity of each serpent presenting stomatitis were collected from fang sheath, using a cotton swab with sterile alginate. The samples were incubated and cultured on Petri dishes containing blood agar and XLD agar using the agar depletion technique. Bacterial growth occurred in all analyzed samples collected from the oral cavity of Bothrops atrox with stomatitis, and some of the samples contained more than one microorganism. The following Gram-negative bacteria were isolated: Escherichia coli (26.31%), Citrobacter spp. (21.05%), Proteus spp. (15.78%) and Salmonella spp. (10.52%). The only Gram-positive bacterium that was isolated was Staphylococcus spp., which was present in 26.31% of the analyzed samples.